The intelligent international negotiator - Karsaklian, Eliane (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
When reading this book you will be familiar with strategies, stories, facts, and tools that intelligent international negotiators use in order to succeed in their negotiations worldwide. The unique integrative cross-cultural approach to negotiating provided by this book will help you to have a different and innovative perception of what negotiating means today. Businesspeople negotiate every day, everywhere around the world. Some are more culturally aware and some are much less. Some forget that negotiation is, first of all, a human interaction. Some still think that negotiation rhymes with competition. But after reading this book, you will approach negotiation from another perspective. More human, more pleasant, and more effective. The Intelligent International Negotiator is a ready-to-use book that you will read and digest very quickly, with inputs you will use immediately.
1. What international negotiation is not -- 2. Merging culture with negotiation -- 3. International negotiating styles -- 4. The international negotiators' toolkit -- Conclusion -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 151-152) and index.
Title from PDF title page (viewed on May 25, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Negotiation; Negotiation in business; BATNA; cultural context; cultural dimensions; cultural intelligence; interculturalist; international negotiator's toolkit; myths; negotiation process; negotiation strategies; win-lose; win-win; Electronic books